Adverse event profile differences among long-acting gonadotropin-releasing hormone analogs: A real-world, pharmacovigilance study - Yuting Chen; Weitao Lu; Ruilian Liao; Ximin Zhang; Wang Chen; Jing Wang; Huancun Feng (PLoS ONE, 2025)
Background Long-acting Gonadotropin-releasing hormone analogs(GnRHa), including leuprolide, goserelin, histrelin, buserelin, triptorelin, have been widely used for a variety of diseases including prostate cancer, breast cancer, endometriosis, uterine leiomyomas, and central precocious puberty (CPP). However, their real-world safety profile differences have not been adequately compared. Objective We aimed to investigate the adverse event (AE) profile differences of long-acting GnRHa reported by the US Food and Drug Administration Adverse Event Reporting System (FAERS). Methods All indications were searched long-acting GnRHa, as primary suspect drugs, from FAERS data (January 2004 to September 2023). We performed disproportionality analyses by reporting odds ratios (ROR) and conducted univariate and multivariate logistical regression analyses to determine the odds ratio (OR) of serious AEs associated with long-acting GnRHa under different exposure factors. Results Reproductive system and breast disorders accounted for the greatest proportion of adverse events among the five long-acting GnRHa formulations analyzed. Both buserelin and histrelin showed distinct adverse effect profiles, with buserelin demonstrating a higher incidence of gastrointestinal disorders and histrelin showing a greater propensity for psychiatric disorders. Logistic regression analysis revealed these five medications carried an elevated risk of significant medical events, and this risk was notably lower in pediatric patients (<18 years) compared to adult populations (≥18 years). Conclusions Significant disparities exist between the adverse event profiles of long-acting GnRHa. The identification of high-risk factors and the enhancement of AEs monitoring are crucial during clinical application.